Diversidad y abundancia de lepidopteros diurnos en el bosque urbano del CIRNA. Loreto - Perú. 2021 - Seopa Vasquez, Segundo Cristian (2023)
This research work was carried out in 2021 and consisted of sampling (3 times a week) for 6 months in the CIRNA urban forest. The objective was to study the diversity and abundance of diurnal Lepidoptera within CIRNA. The capture methodology was through an entomological net and the use of baits made from fruits (ripe). The results provide us with information on the abundance of these species within the CIRNA Urban Forest, 95,7% in the wooded area and 39,1% in the urban area, with a similarity index (Simpson) of 88.8% between zones 1 and 2, with only 5% of diurnal butterfly species in both zones (Bray – Curtis), species richness (Chao -1 “S+”) 25 zone 1 and 15 (zone 2), specific richness of 22 and 9 indicates diversity (Shannon (H)) values of 1,221 and 2,092; in the forest area there is a greater diversity of butterflies (Alpha Fisher) with an index of 3,84 and 4,25, with a dominance of some butterflies as indicated by the Dominance index, with a value of 0,63 and 0,23 zone 1 and 2, 59,9% of zone 1 to favorable conditions and 15,7% adapted to zone 2. Alpha diversity in the forest CIRNA reported 23 species in 5 families, Nymphalidae, Hesperiidae, Riodinidae, Catniidae and Papilionidae, predominating the Nymphalidae family (78,26%) in relation to the other families (21,78%) of species. The largest number of individuals in zone 1 with a proportional abundance of mechanites (899), methona (52), colobura (46), thus, the CIRNA urban forest is a refuge environment for these species.